Emerging Research in Computing, Information, Communication and Applications ERCICA 2016 (Springer Singapore, 2018)
This book presents the proceedings of International Conference on Emerging Research in Computing, Information, Communication and Applications, ERCICA 2016. ERCICA provides an interdisciplinary forum for researchers, professional engineers and scientists, educators, and technologists to discuss, debate and promote research and technology in the upcoming areas of computing, information, communication and their applications. The book discusses these emerging research areas, providing a valuable resource for researchers and practicing engineers alike.